2019
DOI: 10.1016/j.jtcme.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MaquiBright® on improving eye dryness and fatigue in humans: A randomized, double-blind, placebo-controlled trial

Abstract: This study aims to investigate the effects of MaquiBright ® , also known as BrightSight ® , a standardized maqui berry extract, on improving eye dryness and fatigue in Japanese subjects (aged 30–60 years) experiencing eye dryness, eye fatigue, and ≥4 h of visual display terminal (VDT) work daily. Seventy-four participants were equally but randomly assigned to either a MaquiBright ® (MB) or a placebo (P) group, wherein each participant consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 34 publications
1
29
0
3
Order By: Relevance
“…Another study investigated the effects of maqui berry (Aristotelia chilensis) extract in patients with moderate DED, reporting a significant improvement of Schirmer test and quality of life after 60 days of treatments [113]. Similar results were obtained in a randomized controlled trial, which reported a significant improvement in the Schirmer test and symptoms of eye fatigue in visual display terminal users following treatment with maqui berry extract [114].…”
Section: Flavonoidsmentioning
confidence: 73%
“…Another study investigated the effects of maqui berry (Aristotelia chilensis) extract in patients with moderate DED, reporting a significant improvement of Schirmer test and quality of life after 60 days of treatments [113]. Similar results were obtained in a randomized controlled trial, which reported a significant improvement in the Schirmer test and symptoms of eye fatigue in visual display terminal users following treatment with maqui berry extract [114].…”
Section: Flavonoidsmentioning
confidence: 73%
“…Regarding the beneficial health effects of maqui berry, anti-inflammatory [10] [11] [12] [13], anti-diabetic [14], antidepressant [15], anti-obese [16], and memory improving [17] effects have been reported. Moreover, we previously confirmed that maqui berry extract (MBE) possesses excellent ameliorating effects against dry eyes in animal models [18] and clinical trials [19] [20] with Japanese subjects. Moreover, we found that the extract has photoprotective activity in photoreceptor cells in mouse eyes [21].…”
Section: Introductionmentioning
confidence: 78%
“…Seven of the 16 studies used a flavonoid alone (33)(34)(35)(36)(37)(38)(39), and the remaining used mixed supplements (40)(41)(42)(43)(44)(45)(46)(47)(48). The dose of flavonoids ranged from 19 milligrams to 300 milligrams per day.…”
Section: Flavonoids and Ocular Disordersmentioning
confidence: 99%